Forest Policy for the Damodar Valley - Goswami, P. C. (Indian Forester, 1958)
The Lower Damodar Valley region is of vital importance to the Nation. As a result of the D.V.C. undertakings; availability of cheap electrical power, abundance of mineral resources and proximity to the city and port of Calcutta, it has already developed into a highly industrialized region of the country. The continued prosperity of this region is dependent on steps taken to augment the life of the D.V.C. reservoirs and the irrigation canals. The Lower Valley is situated within the State of West Bengal and the Upper Valley where all the forests are, lies within the State of Bihar. The Lower Valley is dependent on the protective functions of the forests of the catchment areas in the Upper Valley, while the main function of the Upper Valley is to generate power. The forest policy for the Damodar Va11ey must recognize and reconcile these somewhat divergent demands. It is seen that about 35 per cent of the total land surface of the Upper Valley is now covered with forests. Because of fire, premature and over exploitation and uncontro11ed grazing, these forests areas are highly eroded and annual increment is very low. If these forests are properly managed, not only can the local demand be met and silt discharge into the reservoirs considerably reduced, but forest products can be supplied to other deficit areas also. Protection and scientific management of the existing forests in the catchment should, therefore, constitute the main plank of the forest policy for the Damodar Va11ey and this work should receive topmost priority. A positive approach to the vexed problem of forest grazing is suggested in the form of pasture development works in parts of the unculturable waste lands. To enable adoption of a longer rotation for production of timber, encouragement to farmers to grow rapid growing trees on their own land is needed. Not more than 2 per cent of the total area of the Upper Va11ey is expected to be available for afforestation. Emphasis, therefore, should shift from afforestation to protection and scientific management of the existing forests. The Government of India, the West Bengal Government, the Damodar Valley Corporation and the Bihar Government have a11 a stake in the forests of the Damodar catchment. It should be their joint effort to adopt and implement a forest policy in conformity with the requirements of the region as a whole.